RELEVANSI KEPEMIMPINAN PERSPEKTIF ISLAM DENGAN DUNIA MODERN: (The Relevance of Islamic Leadership Perspective to The Modern World) - Zaenal Abidin Riam; Selfi Adheleni Putri (Ikatan Sarjana Al-Qur'an Indonesia (ISQI), 2024)
Leadership in the Islamic context is not only an organizational or political responsibility, but also has a profound spiritual and moral dimension. This concept includes principles that can guide leaders to lead fairly, accountably, and empathically towards their leaders. This paper explores various aspects of leadership from an Islamic perspective, focusing on core values such as justice, honesty, openness and accountability to create trustworthy and anti-corruption leadership. This article also describes how the characteristics of leadership that the Prophet Muhammad saw as the primary model of the leadership in Islam. The ideal leader in the Islamic perspective is expected to lead with a noble example and morality, as well as integrity to be able to make decisions based on the principles of Islamic Shariah. In addition, this paper explores the concept of shura as the foundation of consensus-based leadership in Islam, which emphasizes the importance of listening to opinions and paying attention to common interests. The focus in this paper also covers the practical application of Islamic leadership concepts in contemporary contexts, including how these values can be applied in organizational, political, and social management. Thus, this article not only provides a deep understanding of leadership in Islam, but also provides insights into how Islamic universal values may contribute to the construction of a just, harmonious, and sustainable society.